Low and elevated B-type natriuretic peptide levels are associated with increased mortality in patients with preserved ejection fraction undergoing transcatheter aortic valve replacement: an analysis of the PARTNER II trial and registry. (28th December 2019) - Chen, Shmuel; Redfors, Bjorn; O'Neill, Brian P; Clavel, Marie-Annick; Pibarot, Philippe; Elmariah, Sammy; Nazif, Tamim; Crowley, Aaron; Ben-Yehuda, Ori; Finn, Matthew T; Alu, Maria C; Vahl, Torsten P; et al.
Abstract: Aims: B-type natriuretic peptide (BNP) is a cardiac neurohormone that is secreted in response to ventricular volume expansion and pressure overload. There are conflicting data regarding the association between BNP levels and outcomes after transcatheter aortic valve replacement (TAVR). We therefore sought to assess the association between baseline BNP and adverse outcomes in patients with symptomatic, severe aortic stenosis (AS), and left ventricular ejection fraction (LVEF) ≥50%, undergoing TAVR in the PARTNER 2 Trial and Registry. Methods and results: A total of 1782 patients were included in the analysis, and BNP was evaluated both as a continuous log-transformed value and by a priori categories: low (<50 pg/mL), normal (≥50 and <100 pg/mL), moderately elevated (≥100 and <400 pg/mL), or markedly elevated (≥400 pg/mL). Clinical outcomes from discharge to 2 years were compared between patients according to their baseline BNP level, using Kaplan–Meier event rates and multivariable Cox proportional hazards regression models. After adjustment, spline curves revealed a non-linear association between log-transformed BNP and all-cause and cardiovascular mortality in which both the lowest and highest values were associated with increased mortality. Two-year all-cause mortality rates for those with low ( n = 86), normal ( n = 202), moderately elevated ( n = 885), and markedly elevated ( n = 609) baseline BNP were 20.0%, 9.8%, 17.7%, and 26.1%, respectively. In adjusted models, compared to a normal baseline BNP, low [adjusted hazard ratio (HR) 2.6, 95% confidence interval (CI) 1.3–5.0, P -value 0.005], moderately elevated (adjusted HR 1.6, 95% CI 1.0–2.6, P -value 0.06), and markedly elevated (adjusted HR 2.1, 95% CI 1.3–3.5, P -value 0.003) BNP were associated with increased all-cause mortality, driven by cardiovascular mortality. Conclusions: In a large cohort of patients with severe symptomatic AS and preserved LVEF undergoing TAVR, all-cause and cardiovascular mortality rates at 2 years were higher in patients with low and markedly elevated BNP levels. Clinical Trial Registration: https://clinicaltrials.gov/ unique identifier #NCT01314313, #NCT02184442, #NCT03222128, and #NCT03222141.